Estudo comparativo, fisiologica, antropometrico e motor entre futebolistas de differente nivel competitivo - dos Santos, J. A. R. (Revista Paulista Educação Física, 1999)
The aim of this study was to compare the main characteristics of soccer players among athletes of the four national Portuguese divisions. Eighty-nine players of four teams were used as a overall sample. The players were analysed according to the specific positions in the field. The physiological tests used were: VO2max, anaerobic threshold and run economy (all of these tests were performed on treadmill). The anthropometric measures included body composition and somatotype. The squat jump test and the counter movement test were also used as a motor evaluation. The main results show similar characteristics in the four teams in spite of the different competitive levels. A slight non-significant difference was found in the team of lowest level according to some physical parameters. The body fat was not significantly different among the different teams. Concerning aerobic power, the mid-fielders and the lateral players showed the higher values. The defenders and the strikers showed a higher mechanical power in the legs. The main conclusions are: a) the indicators used in this study were unable to discriminate the players according to competitive level; b) the four teams were similar in terms of strength. The differences among players were randomised; c) the analysis according to the specific positions in the field are in accordance with the literature; d) the parameters analysed in this study only suffer slight variations between competitive seasons. full text: http://www.usp.br/eef/rpef/v13n2/v13n2p146.pdf